Women's participation and representation in politics: Perspectives from Ghana - Bawa, Sylvia; Sanyare, Francis (2013)
This article discusses empirical findings on issues affecting women's effective participation in politics and the public sector of Ghana. It argues that women's involvement in public life and politics has steadily declined contrary to hopeful reportage that global empowerment campaigns have increased women's political participation across Africa. The article suggests that given the deep-rooted socio-cultural hindrances women face, affirmative action policies need to be revisited to complement women's agency in contesting for, winning, and participating in politics and public service more effectively. - Reproduced.
Keywords: Women in politics - Ghana; Women in politics